(untitled) (Research, Society and Development, 2025)
The epidemiological analysis of coagulopathies in Brazil between 2017 and 2023 aims to identify the prevalence, patient profiles, and changes in diagnostic patterns over the years, as well as the existence of underdiagnoses. Using registry data, the study seeks to map the incidence of bleeding disorders, including hemophilia, von Willebrand disease, and other rare coagulopathies. The data obtained serve as a basis for future interventions and improvements in the care of patients with bleeding disorders in Brazil. The results are expected to provide a comprehensive overview of the current scenario of coagulopathies in the country, contributing to the development of public health policies for the diagnosis and treatment of patients. Objectives: To analyze the epidemiological trends of coagulopathies in Brazil by assessing the incidence, prevalence, and geographic distribution of these disorders. Methods: This was an analytical, quantitative study based on data collected between 2017 and 2023 in Brazil. Results: The comparative analysis of national data on hereditary coagulopathies between 2017 and 2023 reveals a substantial increase both in absolute numbers and in the proportional representation of various diagnoses. The overall increase of 6,797 cases during the period corresponds to a percentage variation of 26.4%. Conclusion: The numbers in Brazil still indicate significant underdiagnosis, especially in the milder and rarer forms of these conditions. There is a need to strengthen screening actions, professional training, and expand access to specialized diagnosis throughout the national territory.